Fresh chicken eggs preservation under tropical conditions - Lan, Pham Phuong; Lien, Nguyen Xich (The Indian Journal of Animal Sciences, 2012)
Coating materials, mineral oil and alginate were used to determine their effect upon the quality deterioration of chicken eggs during storage under tropical conditions. Eggs (1-day-old) were held at ambient temperature (30Â°C) until 40 days. To evaluate chemical changes, weight losses, Haugh Units, pH (albumen and yolk) and NHâ‚ƒ were measured. Coating with white oil gave the best results with lowest weight losses and highest Haugh unit. Alginate coating did not exhibit a significant effect on Haugh unit record and weight losses compared to untreated eggs. Oiling of eggs preserved quality for 40 days compared to 27 and 24 days for alginate coated and untreated eggs respectively.